Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 8 + (x - 9) = 125 - 64
8 + (x - 9) = 61
x - 9 = 53
x = 62
b. 5 x (X + 7) - 10 = 8 x 5
5 x (X + 7) - 10 = 40
5 x (X + 7) = 50
X + 7 = 10
X = 3
![](https://rs.olm.vn/images/avt/0.png?1311)
A = ( -4/5 + 4/3 ) + (-5/4 + 14/5) - 7/3
= 8/15 + 31/20 - 7/3
= 25/12 - 7/3
= -1/4
B = 8/3 x 2/5 x 3/8 x 10x 19/92
= 16/15 x 15/4 x 19/92
= 4x19/92
= 19/23
C = - \(\dfrac{5}{7}\) x \(\dfrac{2}{11}\) + \(\dfrac{-5}{7}\) x \(\dfrac{9}{14}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{10}{77}\) - \(\dfrac{45}{98}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{635}{1078}\) + \(\dfrac{1}{57}\)
= - \(\dfrac{36195}{61446}\) + \(\dfrac{1078}{61446}\)
= - \(\dfrac{35117}{61446}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)13-2(x+1)=7
2.(x+1)=13-7
2.(x+1)=6
x+1=6/2
x+1=3
x=3-1
x=2
a, 13 - 2 ( x + 1 ) = 7
2 .( x + 1 ) = 13 - 7
2 .( x + 1 ) = 6
x + 1 = 6 : 2
x + 1 = 3
x = 3 - 1
x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 5( x + 7 ) - 10 = 23.5 b) 72 - 7( 13 - x ) = 14
5( x + 7 ) - 10 = 40 49 - 7( 13 - x ) = 14
5( x + 7 ) = 40 + 10 7( 13 - x ) = 49 - 14
5( x + 7 ) = 50 7( 13 - x ) = 35
x + 7 = 50 : 5 13 - x = 35 : 7
x + 7 = 10 13 - x = 5
x = 10 - 7 x = 13 - 5
x = 3 x = 8
c) 5x - 52 = 10 d) 9x - 2.32 = 34
5x - 25 = 10 9x - 2.9 = 81
5x = 10 + 25 9x - 18 = 81
5x = 35 9x = 81 + 18
x = 35 : 5 9x = 99
x = 7 x = 99 : 9
x = 11
~ Hok tốt ~ ( Giờ mik mới thấy bài của bạn ỌwỌ )
a,-1`
b,15 hoặc -15
c, -4
d, -5